Efektivitas Pembiayaan dan Strategi Pengembangan Usaha Paving Blok di PD Telaga Jaya Blok, Tangerang - - Rohayati; Musa Hubeis; Nora Herdiana Pandjaitan (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2015)
Increased industrial development make a positive contribution to the increase in prosperity and welfare of the people and the nation of Indonesia. One of the industrial activity is paving block making business which is the product of a cement building materials that are used as an alternative ground cover or hardening. The objectives of this study were: (1) analyze the quality of block paving based on Indonesian National Standard (SNI); (2) to analyze effectiveness of block paving production cost and (3) to formulate business development strategies for PD Telaga Jaya Blok. This study used primary and secondary data. Analysis were done using internal  external (IE) matrix, analysis strengths, weaknesses, opportunities and threats (SWOT) and quantitative strategic planning matrix (QSPM). Based on laboratory test results of Bina Marga Department Tangerang, blocks paving, kansteen and uskup of PD. Telaga Jaya Blok were good according to  the defined quality standards in Tangerang regency and SNI 03-0691-1996. Analyzes of profitability ratio standard that the PD Telaga Jaya Blok has profitability ratio of 35,38%.  Based on QSPM, then alternative priorities can be sorted, as follows : (1) increase customer loyalty to the block paving products, (2) maintain and improve product quality (3) maintain product selling price  product and (4) provide training to improve the skills of employees